(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
The importance of methodological guidelines aimed at developing students’ speech in teaching native language lessons in primary grades, the need to understand the process of speech and its result, the need to take into account the specific development of students’ cognitive activities, especially the need to pay sufficient attention to work related to their mental and physiological characteristics, as well as a number of recommendations aimed at developing speech are shown. This article provides suggestions and recommendations on this topic, namely, the requirements for students’ speech and the work that should be performed by the teacher at school